How are quality of life ratings made? Toward a model of quality of life in people with dementia. - Byrne-Davis, L; Bennett, P; Wilcock, G (2006)
Quality of life (QOL) has become a focus of research in dementia. In measuring QOL, the views of people with dementia often have not been considered as researchers have proposed that they may not be able to articulate their opinions. This paper counters this belief, presenting a study using a grounded theory methodology to explore the issues that people with dementia felt were important for their QOL. Further, we propose a model of QOL including hypothesised links between important issues (including family and health), QOL and other variables. Twenty-five participants took part in one of nine focus groups. The groups included participants with mild to severe dementia with ages ranging from 49 to 93 years. Results indicate that most of the participants were willing and able to talk about their QOL. Of the 25 participants, only two said that their cognitive problems affected their QOL. Twenty-two issues were discovered through analysis to contribute to QOL, including continuingto live in your own home, independence, spouse and other family, feeling happy and feeling useful. People with dementia used social comparisons in talking about their QOL, as well as direct evaluation of their own happiness. A model of QOL based on theories of coping and response shift is suggested. The fact that so few of the participants talked about disease-orientated issues challenges the large cognitive components included in many QOL measures for use with people with dementia.